Analisa Tingkat Usability Berdasarkan Human Computer Interaction Untuk Sistem Pemesanan Tiket Online Kereta Api - Christanto, Henoch Juli; Sediyono, Eko (Universitas Diponegoro, 2020)
The Current technological developments make PT.Â KAI (Kereta Api Indonesia) as a business entity that regulates and provides rail transportation services has been transformed into providing online ticket reservation services, one of which is through the KAI Access application.Â But it needs to be realized that the marketplace trend has also penetrated travel deals that also provide train ticket reservations, one of which is Traveloka. This interesting phenomenon is the basis for conducting research to see whether the application owned by PT KAI has been able to compete with other applications that also provide online train ticket sales services. By being able to compete, PT KAI can show credibility in providing online ticket transactions. Both applications are tested using the Usability indicators from HCI: Learnability, Efficiency, Memorability, Errors, and Satisfaction.Â This study resulted in a comparison of the two applications by each HCI indicator. The discussion on each indicator it can be seen the classification of the level of usefulness from KAI Access and Traveloka